Empowerment Of Housewive In Family Economy Improvement Through Fishery Products Diversification In Pasaran Island, Teluk Betung Barat, Bandar Lampung - Desy Sasri Untari (Universitas Nahdlatul Ulama Lampung, 2021)
Abundant fishery resources of Indonesia because of water area wider than mainland. In the fact, most of people of coastal area still under poverty. Some factors, such as limitations of knowledge about fishery products management and fishing technology as caused factors of household head low income in daily need fulfilment. Lack of income in daily need fulfilment as motvation of women, wive, or fisherman housewive to help met household needs that increased day to day. Goal of community dedication activity (PKM) to transferknowledge about processing, packaging, and marketing fishery diversification product as an effort to increase economic value in effect community welfare. Method used was through sosialization and practice making diversification fishery products in housewive fisherman. Based on this activity concluded that fisherman house knowledge about processing, packaging, and marketing diversification products such as mackerel fish ball and nugget were increased. they also took innitiative to develop diversification product used abundant fish raw ingridient in its season, but inneconomist price.